Perancangan Website E-Commerce Berbasis OpenCart untuk Pemesanan Kerajinan Tangan di Kabupaten Pesisir Selatan - Anggi Candra, Dwi; Annas, Firdaus; Pahlevi Pane, Reza (Yayasan Lembaga Studi Makwa, 2024)
The advancement of information technology has had a significant impact on the world of trade, including in the marketing of local products. One form of applying technology in this sector is e-commerce websites, which enable online transactions. This research and development (R&D) aims to design an OpenCart- based e-commerce website that can be used by the community in Pesisir Selatan District to market local handicrafts online. The method used in this research is R&D with a prototyping approach, which includes needs analysis, user interface design, system development, and testing and evaluation of the developed website. The designed website provides features such as a product catalog, shopping cart, payment system, and shipping options, which aim to facilitate transactions between sellers and buyers. The result of this R&D is an effective e-commerce website that supports online transactions of handicraft products, increases the accessibility of handicraft products to consumers outside of Pesisir Selatan District. With this system in place, it is expected to increase sales and help handicraft entrepreneurs expand their market. The conclusion of this study is that using the OpenCart platform in the design of e-commerce websites can be an appropriate solution for the development of handicraft businesses in Pesisir Selatan District..